Relation between central aortic pulse pressure and coronary artery disease: a coronary angiographic study in a tertiary care center - Subramanyam, K.; Suranagi, Manohar J.; Subramani, K. S.; Rangaraj, R. (International Journal of Advances in Medicine, 2020)
Background: Aortic pulse pressure is a significant marker of cardiovascular morbidity independently of mean blood pressure and pulse pressure of 60 mm Hg should be considered as the threshold at risk both in normotensives and hypertensives. Coronary perfusion is dependent on diastolic blood pressure and patients with CAD may be susceptible to the adverse effects of low diastolic blood pressure. This study conducted to examine the relation between central aortic pulse pressure and the prevalence and extent of CAD. Methods: A cross sectional, hospital-based study conducted in Sri Jayadeva Institute of Cardiovascular Sciences and Research, Bengaluru, among patients undergoing diagnostic coronary angiography. Results: Risk factors like Diabetes, Hypertension, Dyslipidemia and smoking rates were significantly higher in patients with PP of >60 mmHg (p<0.01). In the first group, the ratio of having normal coronaries is higher 61.9% vs 38% and diseased coronaries was lower when compared to the other group 38% vs 98%. In patients with aortic pulse pressure >60 mmHg, 4 patients had left main coronary artery (LMCA) disease, 20 patients had single vessel disease, 11 patients had two vessel disease and 20 patients had triple vessel disease. Conclusions: In this study it was demonstrated aortic pulse pressure of more than 60 mm Hg is associated with significant CAD.